A structural approach to the assessment and development of engineering students’ professional skills - Karstina, Svetlana; Tussupbekova, Ainura; Mussenova, Elmira (Frontiers in Education, 2025)
On-the-job training plays a key role in developing the professional skills and practical experience of students in engineering education programs. In this regard, the aim of this study was to create a toolkit for analyzing the factors that influence the development of these skills and the integration of students into the professional environment. The methodology included surveying three target groups—students, teachers, and employees of companies involved in the implementation of practice-oriented training at universities—as well as testing three updated training modules integrated with practical training. Based on the collected data, regression models were constructed reflecting the influence of four blocks of factors (organization of practice, digital and production resources, educational support, project activity) on the development of skills in the application of engineering equipment and technologies. The most significant predictor was the block of digital and production resources (standardized regression coefficient β = 1.666, p < 0.001, R2 = 0.684 for the experimental group of students), which emphasizes the importance of the technological content of the learning environment. As a result of training using the updated modules, an increase in the level of proficiency in the application of engineering tools and technologies was recorded. The average score for this criterion was 4.52 in the control group and 4.74 in the experimental group. Progress was also noted in key skills such as basic economic and legal knowledge (F6), self-analysis (F9), and planning (F7). This confirms the effectiveness of a structured approach to combining theoretical and practical training. The proposed structured toolkit for analyzing influencing factors, tested through a multilateral survey and pilot implementation, is a key innovation of the study and can be used by universities and companies to modernize workplace training programs.